A green approach towards synthesis and characterization of Ni(II)- and Pd(II)-N- heterocyclic carbene complexes of pincer ligands: their application in catalytic olefin oxidation studies. - S.M Anwarul Haque, Rosenani (Universiti Sains Malaysia, 2015)
Novel silver(I)- and Mercury(II)-N-Heterocyclic Carbene (NHC) Complexes of pincer ligands were successfully synthesized in good yields. The prepared complexes were then used for the transmetallation reactions to synthesize the required Nickel(II)- and Palladium(II)-NHC complexes. All the synthesized compounds were characterized by various spectroscopic and analytical techniques. X-ray crystallographic technique was used to determine the structural orientations of the molecules. The compounds were tested for possible biological and catalytic behavior. Silver(l) and palladium(lI) complexes showed excellent antibacterial and anticancer results.